Reproduksi Kekuasaan Melalui Teks Keagamaan dalam Reproduksi Perempuan - Ahmad Suhendra (Journal of Gender and Social Inclusion in Muslim Societies, 2020)
Islam places women in a respectable position. The status of woman and man are equal before God. What which divides them is only ‘Piety’. This is a revolutionary reformation that Islam has brought for woman compare to their position before its coming where women is seen as an object, property, inferior being and even agent of evil. It is to this society context and practice, this paper argues, that the discrimination interpretation to certain religious texts has to be related.This paper discusses one hadis (prophet’s saying) which stated that (women’s bodily mode, among others), menstruation will decrease women’s religiosity quantification. This hadis is widely interpreted as one form of women’s physical discrimination, on which point woman are prevented to have controll even to their own body, including their right of sexuality and reproduction. But, this paper maintains that there happen a distortion in understading religious text. The hadis should be analyzed from various perspectives and should be encountered with the fact that the Prophet Muhammad had given freedom to women to the extent that women played important role in public life.